Multiple-criteria model for optimal off-road vehicle selection for passenger transportation: BWM-COPRAS model - Pamučar, Dragan S.; Savin, Lazar M. (Vojnotehnički glasnik / Military Technical Courier, 2019)
Introduction/purpose: Adequate evaluation and choice of off-road vehicles used in performing various types of assignments is a very important factor which affects user mobility and safety as well as the quality and efficiency of carrying out transportation activities in the Serbian Armed Forces (SAF). Methods: This paper thus proposes the BWM (Best Worst Method) and the COPRAS (Compressed Proportional Assessment) models for the selection of the optimal off-road vehicle for the needs of the SAF. The relative weight of the criteria used to assess potential off-road vehicles was established using the BWM method. In addition to the COPRAS method which is a component of the basic decision-making model, in this paper, the MABAC (MiltiAttributive Border Approximation Area Comparison) and MAIRCA (MultiAttributive Ideal-Real Comparative Analysis) methods were also applied through result validation. Results: By testing the BWM-COPRAS model on the example of optimal off-road vehicle selection in the SAF, a high rank correlation was achieved. The results were validated through the statistical processing of the results obtained through the implementation of various multi-criteria techniques by applying the Spearman’s rank correlation coefficient. Conclusion: The results display stability of the results of the proposed model in ranking alternatives and prove the feasibility of the proposed approach to handle multi-criteria decision making problems.